Dynamic identification of damage control characteristics of ultra-high performance fiber reinforced concrete. (30th December 2017) - Othman, H.; Marzouk, H.
Highlights: A thorough characterisation of the impact damage tolerance of UHP-FRC is presented. Superior damage control properties of UHP-FRC are addressed experimentally. Significant of increasing fiber volume content on controlling the damage in UHP-FRC is addressed. Random decrement technique is used to detect damage existence. Abstract: An experimental investigation has been conducted to assess the damage control properties of ultra-high performance fiber reinforced concrete (UHP-FRC) in comparison to traditional concrete. Five identical reinforced concrete (RC) plates, with the exception of concrete material, are damaged gradually using repeated impact technique. Damage progression has been evaluated stepwise based on the change in dynamic parameters and validated by visual inspection, midpoint residual displacement and successive number of impact tests to each specimen. Test results showed that UHP-FRC exhibits superior damage characteristics. The damage rate of UHP-FRC materials are approximately in the range of 6–15% the damage rate of normal-strength concrete.